Supplementation of soft drinks with metallic ions reduces dissolution of bovine enamel - Heloisa Aparecida Barbosa da Silva Pereira; Aline de Lima Leite; Flavia de Moraes Italiani; Melissa Thiemi Kato; Juliano Pelim Pessan; Marilia Afonso Rabelo Buzalaf (University of São Paulo, 2013)
OBJECTIVE: The aim of this study was to evaluate the effect of the addition of metallic ions to carbonated drinks on their erosive potential. MATERIAL AND METHODS: Powdered enamel was added to carbonated beverages (Coca-ColaTM or Sprite ZeroTM and shaken for 30 s. The samples were then immediately centrifuged and the supernatant removed. This procedure was repeated 5 times with the beverages containing Cu2+, Mg2+, Mn2+ or Zn2+ (1.25-60 mmol/L). For Coca-ColaTM, the concentration of each ion that exhibited the highest protection was also evaluated in combination with Fe2+. The phosphate or calcium released were analyzed spectrophotometrically. Data were analyzed using ANOVA and Tukey's test (p<0.05). RESULTS: For Coca-ColaTM, the best protective effect was observed for Zn2+ alone (10 mmol/L) or in combination (1 mmol/L) with other ions (12% and 27%, respectively, when compared with the control). Regarding Sprite ZeroTM, the best protective effect was observed for Cu2+ at 15 and 30 mmol/L, which decreased the dissolution by 22-23%. Zn2+ at 2.5 mmol/L also reduced the dissolution of powdered enamel by 8%. CONCLUSIONS: The results suggest that the combination of metallic ions can be an alternative to reduce the erosive potential of Coca-ColaTM. Regarding Sprite ZeroTM, the addition of Cu2+ seems to be the best alternative.